Productivity growth and finance: The role of intangible assets - a sector level analysis - Demmou, Lilas (OECD Economics Department Working Papers, 2019)
Investment in intangible assets has become an increasingly important driver of productivity growth in OECD countries. Facing stronger informational asymmetries and harder to value collateral, intangible investment is subject to more severe financial constraints and relies more on internal rather than external capital. To test the hypothesis that the availability of finance, and financial development in particular, is more important for productivity growth in sectors that are intensive in intangible assets, an empirical analysis is carried over a panel of 32 countries and 30 industries, from 1990 to 2014. Overall, results confirm that the impact of financial development on labour productivity is not uniform across sectors. It varies based on country-specific institutional settings and sector-specific characteristics such as the intangible asset intensity, financial structure and external financial dependence. Policies and institutional settings may relax financial constraints by: i) altering the overall composition of finance; ii) encouraging competition and iii) strengthening the legal environment in which businesses operate